HYBRID MANUFACTURING FRAMEWORK TO IMPROVE SMALL TO MEDIUM-SIZED MANUFACTURERS’ FLEXIBILITY TO MARKET TURBULENCE IN A MULTI–PRODUCT ENVIRONMENT: CASE STUDY OF A MANUAL ASSEMBLY LINE - Mukalay, Thierry Abedi (The South African Journal of Industrial Engineering, 2020)
Market flexibility can be described as the ability to react competently to customers’ fluctuating demands. This ability has become critical to the survival of small to medium-sized enterprises. This study aimed at improving small to medium-sized manufacturers’ flexibility. The framework proposed in this paper has a mixed make-to-order and make-to-stock strategy, supported by a manual assembly line setup based on workers’ movements at its core. The hybrid system designed through this study allows small to medium-sized manufacturers to improve their responsiveness to the current dynamically changing market environment, and to stay competitive by providing them with the tools for fast customer response and financial expansion.